Blanket design studies for maximizing the discharge burnup of liquid metal cooled ATW systems - Yang, Won Sik (Annals of nuclear energy, 2002)
This paper presents the results of neutronic design studies of lead–bismuth eutectic (LBE) and sodium cooled accelerator transmutation of waste (ATW) blankets. These studies have focused primarily on maximizing the discharge burnup under key thermal-hydraulic and material-related design constraints. Subject to the design constraints on the peak linear power, the maximum coolant velocity, the maximum volume fraction of transuranic (TRU) elements in the dispersion fuel, and the peak fast fluence, design studies have been performed for 840 MW ATW blankets. From these studies, it has been found that the unconstrained discharge burnup for a fixed fuel residence time increases monotonically as the fuel volume fraction and blanket size decrease. The results also show that the discharge burnup is proportional to the peak fast fluence. These indicate that the maximum discharge burnup is primarily determined by imposed design constraints. The maximum discharge burnup achievable under the peak fast fluence limit has been found to be ∼28% for the LBE system, and ∼30% for the sodium system. The optimum fuel volume fraction appears to be ∼0.21 and ∼0.32 for LBE and sodium systems, respectively.